Utilization of TVP and agar for a low-fat, fiber-rich chicken burger patty - Reyes, Riechie Rayos
ABSTRACT The study was done to utilize agar and TVP to produce low-fat, fiber-rich chicken burger patties. The study was divided into four phases. Phase I was the selection of the most acceptable formulation. The data obtained were analyzed using the Kramer's Rank Sum Test (α=0.05).Phase II determined the optimum levels of TVP and agar. Nine samples with varying levels of TVP (0, 20 and 40%) and agar (0, 2 and 4%) were presented to 12 panelists with a descriptive hedonic scale score shhet. The data obtained were analyzed using ANOVA and DMRT (α=0.05). The formulation chosen was the one with 20% TVP and 2% agar. Phase III tested the reproducibility of the TVP-substituted and agar-incorporated chicken burger patties and was done in the three batches at bench scale. The analysis was done using ANOVA (α=0.05) which showed no significant difference among the three production batches. Phase IV was the physico-chemical and cost analyses of the control and experimental chicken burger patties. The control chicken burger patties contained 57.20% moisture, 12.50% crude fat, 23.55% protein, 7.65% available carbohydrates, 0.26% crude fiber and 3.05% ash while the experimental chicken burger patties contained 59.40% moisture, 10.50% crude fat, 20.05% protein, 7.55% available carbohydrates, 0.385% crude fiber and 3.10% ash. In the experimental formulation, fiber content increased while the fat content decreased but not enough for it to become a low-fat, high-fiber product. The cost of a 50-g patty of the control formulation is Php 6.88 while that of the experimental formulation is Php 8.72.